Polycyclic Indolines by an Acid‐Mediated Intramolecular Dearomative Strategy: Reversing Indole Reactivity in the Pictet‐Spengler‐Type Reaction. Issue 21 (13th September 2018) - Ciccolini, Cecilia; Mari, Michele; Lucarini, Simone; Mantellini, Fabio; Piersanti, Giovanni; Favi, Gianfranco
Abstract: Indoline‐fused polycycles were synthesized through a TFA‐promoted intramolecular dearomative cyclization of indole‐tethered pyrroles. Mechanistically, the strategic carbon‐carbon bond formation is hypothesized to proceed via a Pictet‐Spengler‐type reaction wherein a reversal of conventional indole reactivity of tryptamine derivatives occurs. The synthetic versatility of this operationally simple, atom‐economic approach is demonstrated in the preparation of the pyrido[1, 2‐ a :3, 4‐ b′ ]diindole core of natural product homofascaplysin C. Abstract :